Relationship between moose (Alces alces) home range size and crossing wildlife fences - Sjöberg, Jerk (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2013)
Wildlife fences are today commonly used along highways to reduce the risk of vehicle collisions with wildlife. Since traffic and roads have expanded over the years, wildlife behaviour has become more interesting not only for the prevention of vehicle collisions but also to understand how human activities impact their natural habitats. Moose is one of those animals that have increased in interest in such studies. In this study, I tested if the probability to cross wildlife fences of moose would increase with increasing home range sizes, and also at what time of the year they cross. The study area is situated in Nordmaling municipality, located in Northern Sweden in the County of Västerbotten. Data from 2004/2005 with GPS positions of every hour from 18 moose individuals were used in this study. A normal 95% kernel utilization distribution (UD) was used to identify home range area of each individual and a general linear model (GLM) was used in analysis of home range area against response variable of crossings. To estimate which time crossings occurred over the year, a generalized linear mixed model (GLMM) was used. The results showed no effect of different home range sizes on the probability of crossing the fence. A difference over time and year was detected, with a more even distribution throughout the day in January compared to i.e. April and May which had a two sided distribution with most crossings in the morning and evening. I recommend future research to use more data and investigate how other factors like planned crossing areas passes affects the movement behaviour of moose. Viltstängsel är idag vanligt längs med vägar för att minska risken för viltolyckor. Eftersom trafikmängd och vägar har ökat med åren, har även intresset för djurs beteendemönster ökat och inte bara för att förebygga viltolyckor utan också för att förstå hur människan påverkar deras naturliga miljö. Ett av dem djur som har ökat i intresse inom naturvetenskapliga undersökningar är älgen. I den här studien testades älgars ...